2017
DOI: 10.1051/ject/201749273
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Blood Product Conservation: Results of Strategies to Improve Clinical Outcomes in Open Heart Surgery Patients at a Tertiary Hospital

Abstract: Blood product usage is a quality outcome for patients undergoing cardiac surgery. To address an increase in blood product usage since the discontinuation of aprotinin, blood conservation strategies were initiated at a tertiary hospital in Oakland, CA. Improving transfusion rates for open heart surgery patients requiring Cardiopulmonary bypass (CPB) involved multiple departments in coordination. Specific changes to conserve blood product usage included advanced CPB technology upgrades, and precise individualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Ottens, et al, [22] conducted a randomized trial to investigate the role of inline blood gas monitoring in improving perfusion management during CPB [22]. The study utilized the CDI™500 device for Furthermore, Khan, et al, [23] reported on the implementation of blood conservation strategies in open-heart surgery patients requiring CPB [23]. By employing multiple departments in a coordinated effort, this aimed to improve transfusion rates and reduce blood product usage.…”
Section: Quality Improvement Initiativesmentioning
confidence: 99%
“…Ottens, et al, [22] conducted a randomized trial to investigate the role of inline blood gas monitoring in improving perfusion management during CPB [22]. The study utilized the CDI™500 device for Furthermore, Khan, et al, [23] reported on the implementation of blood conservation strategies in open-heart surgery patients requiring CPB [23]. By employing multiple departments in a coordinated effort, this aimed to improve transfusion rates and reduce blood product usage.…”
Section: Quality Improvement Initiativesmentioning
confidence: 99%